Kopplingen mellan attityd och förvaltning - Wahlund, Sandra (2019)
Large carnivores have gone from near extinction to viable populations during the past decades. Public opinion concerning large carnivores has also shifted during the same timeline, from a general positive attitude to a more negative, especially in those areas where the carnivores re-emerged.